2013
DOI: 10.1097/inf.0b013e3182a0960b
|View full text |Cite
|
Sign up to set email alerts
|

Hoarseness as a Presenting Sign in Children With Kawasaki Disease

Abstract: We noted that many patients with Kawasaki disease (KD) were hoarse at presentation and thus evaluated the frequency of hoarseness in children with acute KD. New onset hoarseness was noted in 86 of 287 (30%) prospectively assessed KD patients. Laryngoscopic examination of three hoarse patients with acute KD revealed edema and erythema of the larynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…In this study of Latin American children with KD, we found a lower frequency of hoarseness during the acute phase than in the only previous report by Leuin et al 1 .We found a lower frequency of hoarseness during the KD acute phase in our study compared to the previous report in a single US population by Leuin et al . (11.6 % vs 30% respectively), where KD patients with hoarseness were younger than those without it (1.9 vs 3.1 years) 1 . Similarly, we observed that hoarse KD patients were younger (median age 18 vs 26 months).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In this study of Latin American children with KD, we found a lower frequency of hoarseness during the acute phase than in the only previous report by Leuin et al 1 .We found a lower frequency of hoarseness during the KD acute phase in our study compared to the previous report in a single US population by Leuin et al . (11.6 % vs 30% respectively), where KD patients with hoarseness were younger than those without it (1.9 vs 3.1 years) 1 . Similarly, we observed that hoarse KD patients were younger (median age 18 vs 26 months).…”
Section: Discussioncontrasting
confidence: 61%
“…Thus, hoarseness could be present even in the absence of a viral co‐infection as a part of a systemic disease with inflammation in immunological diseases. In KD hoarseness patient association with earlier diagnosis and higher band count suggest that hoarseness may be a result of a more severe systemic inflammation involving the larynx 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have established that host genetics influence susceptibility and disease outcome, the etiologic agent that triggers KD remains elusive, and extensive searches for an infectious agent have not yielded a consistent pathogen. Several lines of evidence suggest an upper respiratory tract portal of entry for the environmental trigger of KD including inflammation of the tissues of the oropharynx and upper airway and infiltration of the bronchi by IgA-secreting plasma cells 6 8 . An antecedent minor infection associated with immune activation followed by an environmental exposure to a specific trigger have been postulated as a sequence that can induce the vasculitis in genetically susceptible children 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Clinical features of the illness, including mucosal inflammation of the lips, tongue, and upper airway coupled with cervical lymphadenopathy and hoarseness, all point to a trigger that enters through the nasopharynx. 4 , 5 Specific atmospheric patterns have been linked to clusters of cases of Kawasaki disease that may increase exposure to the causative trigger. 3 …”
mentioning
confidence: 99%